COVID-19 associated renal artery stenosis in infancy - A report of two cases - Sataroopa Mishra; Saurabh Kumar Gupta; Sivasubramanian Ramakrishnan; Shyam Sunder Kothari; Anita Saxena; Sanjeev Kumar (Wolters Kluwer Medknow Publications, 2023)
Organ-specific vasculitis is an uncommon, delayed complication of COVID-19 infection. It is usually seen in mildly symptomatic or asymptomatic patients. Underlying endothelitis is the most likely pathophysiological mechanism for such a manifestation. We report two infants with renal artery stenosis, most likely consequent to COVID-19 infection.